Adipositas & Bewegung - Kemmler W; Teschler M; Weissenfels A; Willert S; Bebenek M; von Stengel S (Dynamic Media Sales Verlag, 2017)
Sarcopenia and sarcopenic-obesity (SO) are key risk factors for disability, loss of independence and morbidity in older people. Although most studies confirm the positive impact of resistance training on muscle mass and functional capacity, the majority of older people fall far short of the exercise doses recommended topositively impact muscle mass or disabling conditions. For these persons, whole-body-electromyostimulation (WB-EMS) may be a time-efficient, physically less exhausting and joint-friendly option to increase lean-body-mass (LBM) and to reduce fat-mass. In this narrative review, we summarize the effects of WBEMS on body composition with special regard to sarcopenia and SO. Further, possible mechanisms of WB-EMS-induced increases of energy expenditure are discussed.The majority of WB-EMS studies reported significant positive effects on lean-body and fat-mass in older adults. The few studies that focus on sarcopenia consistently determined improvements inmorphometric and functional dimensions (i.e. gait-speed and /or handgrip-strength). The corresponding effect on (sarcopenic) obesity was less consistent. However, studies that applied WBEMS at higher intensities reported predominantly significant acute-, short- and long-term increments of energy expenditure. Low doses of protein supplements (0.33g/kg/d; total intake: >1.2-<1. 5g/kg/d) were unable to enhance the WB-EMS-induced effect on sarcopenia parameters.In summary, WB-EMS can be seen as an effective method for fighting sarcopenia and sarcopenic obesity in older people who are unable to performintense exercise protocols. The role of additional protein supplements needs to be addressed in subsequent studies.KEY WORDS: Sarcopenia, Obesity, Electromyostimulation, Lean Body Mass, Body Fat, Older People